Eksodus dari Bumi Hangus: Peristiwa Keluarnya Penduduk Dari Timor Timur Pasca Jajak Pendapat 1999 - Jerwin Jerwin; M. Rasyid Ridha; Ahmadin Ahmadin (Pendidikan Sejarah Fakultas Ilmu Sosial Fakultas Ilmu Sosial, 2017)
This paper is about to explain the incident of the East Timorese who moved to Pangkep District, due to the riots after the announcement of the results of the Popular Consultation in the area. The situation became tense and caused insecurity among the people of East Timor. Including the migrants, from various regions of Indonesia such as Pangkep District. Pangkep people who have stay for a long time in East Timor, in general already have some valuable assets. Such as land, house, shop, and vehicle. But unfortunately, their assets were left behind, before being sold. The problem of the assets of the newcomers is then required to be resolved immediately. The study of the East Timor Exodus in Pangkep District is interesting because the arrival of migrants in East Timor and their return after the referendum has not been specifically studied. Especially coming from South Sulawesi, especially Pangkep regency. This research is a qualitative research with Historical Research approach, which consist of several stages: (1) Heuristic, by interviewing some East Timor Exodus people like Hasan, Salma, Muhris, etc. Collecting records at the Pangkep District Social Service, data held by the National Committee for East Timor Police Victims of Pangkep District, and in the November 5, 2016, issue of the Daily Fajar newspaper. It also used books related to East Timor, population and societal studies (Sociology / Anthropology). (2) Criticism or verification process of authenticity of historical sources. (3) Interpretation or interpretation of historical sources, and (4) Historiography, is the stage of historical writing.